Deworming among pre-school and school going children in a rural area: a cross-sectional survey - Gupta, Manish Kumar; Singla, Shweta (International Journal Of Community Medicine And Public Health, 2017)
Background: Morbidity due to Soil transmitted helminth (STH) infections can be controlled at a reasonable cost by means of mass deworming using effective drugs. Deworming campaigns targeted at high risk groups, such as school-age children, pre-school children and women of child-bearing age are the mainstay of the control strategy launched by WHO. Methods: A small sector was surveyed on the National Deworming Day (NDD) to record the percentage coverage of children in pre-school and school going children. Children were observed for any of the adverse effects within 24 hrs of taking Albendazole. Results: Out of the total of 1142 children in anganwadis and government schools of the study area, 993 (86.9%) received tablet Albendazole (400 mg) under supervision of teachers. Among these only 3 children (0.26%) reported with adverse effects like vomiting and dizziness. Conclusions: The percentage coverage of children on the NDD was about 87%. Ministries of Health can set up efficient, safe delivery, monitoring and referral systems, in order to minimise the risk and maximise the benefit of periodic deworming and increase the percentage coverage in communities where soil-transmitted helminthiasis is endemic.